2002
DOI: 10.1021/ma010497c
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of Polyaniline and Na+−Montmorillonite Clay

Abstract: Nanocomposites of conducting polyaniline (PAN) with inorganic Na + -montmorillonite (MMT) clay were synthesized by the emulsion polymerization method. The dodecylbenzenesulfonic acid (DBSA) was used for both dopant and emulsifier. Analyses of X-ray diffraction patterns demonstrated that conducting PAN-DBSA was intercalated between inorganic clay layers at the nanoscale level (<10 Å). We observed that the clay induced more disordered state in PAN-DBSA/clay nanocomposites. From the temperature-dependent dc condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(97 citation statements)
references
References 32 publications
2
94
1
Order By: Relevance
“…[44][45][46][47][48][49] Hybrid electrochromic films based on NiO and polyaniline (PANI) have shown fast operation, high stability and a remarkable efficiency of 85 cm 2 C…”
Section: 43mentioning
confidence: 99%
“…[44][45][46][47][48][49] Hybrid electrochromic films based on NiO and polyaniline (PANI) have shown fast operation, high stability and a remarkable efficiency of 85 cm 2 C…”
Section: 43mentioning
confidence: 99%
“…The powders of inorganic oxides, like silicon dioxide [40,41], titanium dioxide [42], copper(II) oxide [43], and ferrites [44], may serve as examples of another group of materials which have been modified on the surface with PANI. Special attention has been paid to montmorillonite and related clays [45][46][47][48]. The applications of surface-modified substrates range from sensors and electronic noses [18,49], electrodes [30,50], conducting fillers [51], electro-rheological suspensions [42,48,52], corrosion protection [45], gas-separation membranes [29], and catalysis of organic reactions [53] to electromagnetic interference shielding [34] or increasing the dielectric breakdown of polymer films [28].…”
Section: Introductionmentioning
confidence: 99%
“…After the observation of PANI intercalation into Cu 21 exchanged silicates by Cloos et al in 1979, 19 a number of studies on the preparation, properties and applications of PANI/layered silicate nanocomposites were carried out. [10][11][12][13][14][20][21][22][23][24][25][26][27][28] Most recently, Yang and Chen reported the synthesis of PANI/ organically modified clay nanocomposites and found that more PANI chains are formed between interlayer spacings of the modified clay, especially for HOOC(CH 2 ) 11 NH 3 1 modified clay because the acidic HOOC(CH 2 ) 11 NH 3 1 ions residing between interlayer spacings provide a stronger driving force for the intercalation of aniline monomer. 29 Yeh et al reported that regardless of clay content, the synthesis of PANI/clay nanocomposites with exfoliated silicate layers of clay was realized and they investigated the effect of such nanocomposites on the corrosion protection of cold rolled steel (CRS) when compared with that of an emeraldine base of PANI using a series of electrochemical measurements of corrosion potential and polarization resistance.…”
Section: Introductionmentioning
confidence: 99%